Quality improvement of lime fruit (Citrus aurantifolia) between packaged and unpackaged conditions combined with different storage temperatures - Habibi, Irfan; Susila, Anas Dinurrohman (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The use of limes is increasingly widespread worldwide, both as fresh fruit for consumption and for making juice or other drinks. Lime is also used in making jams and candies. The essential oil obtained from the skin is widely used in the pharmaceutical and cosmetic industries for medicines, perfumes, soaps, body lotions, and detergents. However, during fruit storage, the respiration and metabolic activity in lime fruits is directly related to the increase in ambient temperature, which makes the fruit dry out. Improving the shelf life of lime against post-harvest stress while maintaining the sensory and nutritional qualities of fresh produce can be achieved through low-temperature storage and the use of packaging. This study aims to improve the quality of lime by knowing the difference between the provision of packaging and not-given packaging combined with different storage temperatures. Method: The experimental design used a single-factor completely randomized design with storage type treatment, which includes room temperature without packaging (control), room temperature with packaging, low temperature without packaging, and low temperature with packaging. Observations of non-destructive characteristics include weight loss, respiration rate, and fruit peel color. Observations of destructive characteristics include juice content, fruit peel softness, Soluble Solid Contents (SSC), Total Acidity (TA), SSC/TA ratio, and ascorbic acid content. Findings: Low temperature treatment without packaging provides the best results in delaying weight loss, respiration rate, and SSC/TA ratio. The control treatment provided the best results for peel softness, juice content, and ascorbic acid. Conclusion: Low temperature treatment without packaging is recommended for the storage of lime fruit to extend its shelf life. Novelty/Originality of this Study: This study examines the combined effects of low temperature and newspaper packaging on extending the shelf life of lime fruits, addressing a significant gap in postharvest storage research for non-climacteric fruits such as lime.